Cluster Cover Page (Synlett, 2013)
The concept of an organic superbase is relatively recent, and the range of molecules possessing this property continue to provide us with previously undreamt of chemical reactivity. The work described in this cluster shows how the legacy of chemists such as Manfred Schlosser lives on. Furthermore, this Cluster project has given me the chance to work once more with my dear friend and respected colleague, Tsutomu Ishikawa. I wish him well in his impending retirement. Laurence M. Harwood